The Role of Productivity in the Relationship Between Ergonomics and Sustainable Performance of Food MSMEs: - - Rahmatul Lael; Hilma Raimona Zadry; Alizar Hasan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Food-based MSMEs face challenges in improving productivity and sustainability due to production processes that remain dominated by manual activities. The application of ergonomics is one approach to supporting increased productivity and business sustainability. This study aims to analyze the effect of ergonomics on sustainable performance through the role of productivity in food MSMEs in Payakumbuh City. This study uses a quantitative approach involving 92 food MSME operators, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that ergonomics positively affects productivity and sustainable performance. Productivity also mediates the relationship between ergonomics and sustainable performance in food MSMEs. Implementing ergonomics and improving productivity need to be part of efforts to develop sustainable food MSMEs. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production